Design specifications for biomedical virtual twins in engineered adoptive cellular immunotherapies - Ulrike Weirauch; Markus Kreuz; Colin Birkenbihl; Miriam Alb; Maria Quaranta; Laurence Calzone; Sophia Orozco-Ruiz; Stefanie Binder; Luise Fischer; Solène Clavreul; Morine Maguri; Maximilian Ferle; et al. (npj Digital Medicine)
Abstract In (immune)oncology, virtual twins (VTs) offer patient-individual decision support. Nevertheless, current VTs do not incorporate the unique properties of engineered adoptive cellular immunotherapies (eACIs). Here, we outline the minimal design specifications for VTs for engineered ACIs (eACI-VTs) to model the complex interplay between cell product and patient physiology. We motivate utilizing VTs in eACIs to provide decision support and reflect on how eACI-VTs can support the widespread use of eACIs.